2023
DOI: 10.1101/2023.04.17.537218
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

5-ASA can functionally replace Clostridia to prevent a post-antibiotic bloom ofCandida albicansby maintaining epithelial hypoxia

Abstract: Antibiotic prophylaxis sets the stage for an intestinal bloom ofCandida albicans, which can progress to invasive candidiasis in patients with hematologic malignancies. Commensal bacteria can reestablish microbiota-mediated colonization resistance after completion of antibiotic therapy, but they cannot engraft during antibiotic prophylaxis. Here we use a mouse model to provide a proof of concept for an alternative approach, which replaces commensal bacteria functionally with drugs to restore colonization resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Notably, increased epithelial oxygenation after Clostridia depletion drove a postantibiotic C. albicans expansion. Commensal Clostridia species could be replaced functionally with 5-aminosalicylic acid (5-ASA), which activated mitochondrial oxygen consumption to restore epithelial hypoxia and reinstate colonization resistance against C. albicans (Savage et al 2023 ). Thus, 5-ASA treatment is a nonbiotic intervention that restores colonization resistance against C. albicans .…”
Section: Scientific Programmementioning
confidence: 99%
“…Notably, increased epithelial oxygenation after Clostridia depletion drove a postantibiotic C. albicans expansion. Commensal Clostridia species could be replaced functionally with 5-aminosalicylic acid (5-ASA), which activated mitochondrial oxygen consumption to restore epithelial hypoxia and reinstate colonization resistance against C. albicans (Savage et al 2023 ). Thus, 5-ASA treatment is a nonbiotic intervention that restores colonization resistance against C. albicans .…”
Section: Scientific Programmementioning
confidence: 99%
“…biofilm and hyphal development [41]. A recent pre-print article identified that the ubiquitous UC treatment 5-aminosalicylic acid can reduce post-antibiotic C. albicans bloom, which is thought to be promoted by the restoration of mucosal hypoxia and gut re-colonisation by Clostridia [42]. Separately, Candida tropicalis levels appear to be positively correlated with several pathogenic bacteria within the guts of CD patients, and their co-existence within biofilms is associated with more filamentous growth [9].…”
Section: The Mycobiomementioning
confidence: 99%